Galactose-Deficient IgA1 Deposits in Clear Cell Renal Cell Carcinoma-Related Henoch–Schönlein Purpura Nephritis - Yuhong Zhao; Youngki Kim; Milind Junghare; Viral Vakil; Xuesong Su; Faqian Li; Lihong Bu (Case Reports in Nephrology)
Recent studies suggest that galactose-deficient IgA1 (Gd-IgA1) plays a role in the pathogenesis of primary IgA nephropathy (IgAN) and Henoch–Schönlein purpura nephritis (HSPN). Furthermore, immunostaining of KM55, an antibody that identifies Gd-IgA1, may be helpful to differentiate primary IgAN and HSPN from secondary causes of glomerular IgA deposition. We report sequential kidney biopsies of a malignancy-associated HSPN, showing intense glomerular mesangial IgA deposition at the initial kidney biopsy and dramatic decrease in disappearance of glomerular deposits after tumor removal. We demonstrate that the glomerular IgA deposition contains Gd-IgA1, detected by immunostaining of KM55, with similar distribution and intensity to IgA. This suggests that renal Gd-IgA1 deposition may play a role in the pathogenesis of malignancy-associated HSPN.